RUNX proteins in development and cancer - Groner, Yoram; Ito, Yoshiaki; Liu, Pu Paul; Neil, James C; Speck, Nancy A; Van Wijnen, Andre J. (Springer, 2017)
"This volume provides the reader with an overview of the diverse functions of the RUNX family of genes. As highlighted in the introduction and several of the 29 chapters, humans and other mammals have three RUNX genes that are known to play specific roles in blood, bone and neuronal development. However, their evolutionary history has recently been traced back to unicellular organisms and their involvement in many well-known signaling pathways (Wnt, TGFb, Notch, Hippo) is indicative of a more general function in cell biology. Their documented roles in cell fate decisions include control of proliferation, differentiation, survival, senescence and autophagy"--Publisher's description.
Keywords: DNA-binding proteins -- Cancer -- Research.; Life sciences.; elektronické knihy; electronic books